Rancang Bangun Pengontrol Beban Listrik Menggunakan Perintah Suara Melalui Smartphone Android Berbasis Arduino Nano - Wibowo, Lastoni; Putro, Dwi Purnomo (SIMETRIS, 2023)
Electrical Loads are electrical equipment that is attached to the electrical system in a house or building. The operation of electrical equipment generally still uses a mechanical switch. The use of mechanical switches is considered less effective because controlling electrical equipment must be done directly through the switch. In this research, a prototype controller of an electric load was designed and built through voice commands given via an Android smartphone. The prototype made is based on the Arduino nano microcontroller. The prototype made is capable of controlling 10 electrical loads with a load capacity of 200 Watt each. The trials that have been carried out show that the prototype is able to execute voice commands with a success rate of 91%.